KEKUATAN PEMBUKTIAN SERTIFIKAT DALAM SENGKETA HAK ATAS TANAH - Ramli Usman; Ilyas Ismail; Azhari Yahya (Jurnal Ilmu Hukum, 2016)
Abstract: Certificate is an evidence tool based on Article 19 of the Act Number 5 Year 1960 regarding to the Fundamental Rules of Agrarian (UUPA). However, in practice, the evidence degree of land owning certificate might be nullified by the evidence of opponent which was an underhand deed like a civil case Number 04/Pdt.G/2009/PN-Sgi so that the letter from the head of village brought by the prosecutor to the court could able to defeat the Usage Right Certificate that was brought by the defendant in the court. Normative law method was used in this research. The results showed that the evidence degree of the Usage Right Certificate Number 02 Year 1986 really depended on the belief and trust of the judges on the correct procedure of getting the Usage Right Certificate and the ability of the defendant in providing land book of the certificate in the court. Although the defendant had provided the certificate to prove that the disputed land was legally owned showing from the legal land certificate, but if the judges did not believe the defendant, the certificate was then finally determined by the judges as an illegal and had no legal binding.  Keywords: Degree of evidence, certificate, land right. Abstrak: Sertifikat merupakan alat pembuktian menurut Pasal 19 Undang-Undang Nomor 5 Tahun 1960 tentang Peraturan Dasar Pokok-pokok Agraria (UUPA). Namun dalam prakteknya kekuatan pembuktian sertifikat hak atas tanah dapat dipatahkan oleh alat bukti lawan berupa akta di bawah tangan, seperti dalam kasus perdata No.04/Pdt.G/2009/PN-Sgi sehingga Surat Keterangan Kepala Desa yang disampaikan oleh penggugat kepada Majelis mampu mengalahkan alat bukti Sertifikat Hak Pakai yang disampaikan oleh tergugat di persidangan. Penelitian ini menggunakan metode penelitian hukum normatif. Hasil penelitian menunjukkan bahwa kekuatan pembuktian Sertifikat Hak Pakai Nomor 02 Tahun 1986 ternyata sangat tergantung kepada keyakinan dan kepercayaan hakim terhadap kebenaran prosedur perolehan sertifikat hak pakai dan kemampuan tergugat dalam menghadirkan buku tanah/warkah dari sertifikat tersebut ke persidangan. Walau pihak tergugat telah memberikan data untuk menguatkan bahwa tanah sengketa telah dikuasai dengan cara sah bahkan telah memperoleh sertifikat hak atas tanah, namun apabila Majelis tidak mempercayainya, sertifikat tersebut akhirnya tetap dinyatakan oleh majelis cacat hukum dan tidak mempunyai kekuatan hukum.Kata Kunci : Kekuatan pembuktian, sertifikat, hak atas tanah.